La filosofía analítica de Uberto Scarpelli. Del análisis del lenguaje valorativo a los principios de la bioética - Zorzetto, Silvia (Pontificia Universidad Católica del Perú. Fondo Editorial, 2014)
It is a biographical article about Uberto Scarpelli and its main aim is to give a philosophical scheme of Scarpelli, commenting the most important aspects of his life, his main works and the itinerary of his thought. The article depicts as a transversal idea that for Scarpelli there is no side study between philosophy and the General Theory of Law; quite the contrary, both of them are always in complete joining and mutual feedback. That is the reason why the article shows a scarpellian sight of language analysis, epistemology, ethical deliberation and General Theory of Law.

El presente trabajo es un artículo biográfico sobre Uberto Scarpelli. Tiene por objetivo principal proporcionar un mapa de la filosofía de Scarpelli, comentando los aspectos más importantes de su vida, sus principales obras y el itinerario de su pensamiento. El artículo muestro como idea transversal que, para Scarpelli, ningún estudio es lateral respecto de la filosofía y la teoría general del derecho, sino que, por el contrario, proceden siempre en estricta unión y mutua retroalimentación. Es por ello que el texto nos muestra la visión scarpelliana del análisis del lenguaje, de la epistemología, de la reflexión ética y de la teoría general del derecho.
The analytic Philosophy de Umberto Scarpelli. From the analysis of the evaluative language to the principles of bioethics
Keywords: Derecho; https://purl.org/pe-repo/ocde/ford#5.05.00